THE PESANTREN EDUCATIONAL MANAGEMENT AND BUILDING RELIGIOUS ISLAMIC GENERATION - Mawardi Lubis (Universitas Islam Negeri Fatmawati Sukarno, 2015)
The objective of this research was to understand the pesantren educational management and building religious Islamic generation. The approach be used in research was qualitative participant and descriptive analysis method. The data were collected through live explanation by the Bengkulu Islamic Students Pesantren (Ma’had ath-Thullab al-Islami) Dr. H. Mawardi Lubis, M.Pd manager as a unit analysis of the research. The research result indicates that the pesantren have been implementing a traditional and centralistic educational management ( all in kyai management). Than, the pesantren have been gaving good contribution in building religious Islamic generation.